PENGARUH RISIKO BISNIS, STRUKTUR AKTIVA, PROFITABILITAS, LIKUIDITAS DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011-2013 - Nivita Dyah Estuningtyas, 10.05.51.0101 (Students Journal of Economic and Management, 2015)
This study examines the effect of business risk , asset structure , profitability , liquidity , size of the company on the capital structure . This research was conducted in the Indonesia Stock Exchange using perusaaan analysis unit manufacturing that have gone public. The method used in this research is the method of quantitative dskriptif . Engineering samples using purposive sampling technique with a study period of 2011 to 2013. The results of the business risks and asset structure and significant positive effect on capital structure , profitability and significant positive effect on capital structure . Results Liquidity and size or the size of the company and a significant negative effect on capital structure Keywords : Capital Structure , Business Risk , Asset Structure , Profitability , Liquidity and Firm Size .